El Teletrabajo en el Perú: Comentarios al Nuevo Marco Normativo - Ramirez Punchin, Eddy Hills (2016)
This article analyzes the regulatory framework of teleworking. In that sense, we approach different definitions to finally establish the definition and formalities required according to our legislation. We will reflect about the problems that telework pretends to solve, so we can establish then if we have the minimum standards that allows the use according to our labor rights or whether there is a poor regulation in relation to safety and health at work and labor inspections, for that reason we propose some alternatives solutions for above mentioned deficiencies.